Correlation of Procalcitonin with Hematological Markers in Patients with SIRS and Sepsis: An Observational Study - Saini, Tushar Krishnan; Suryavir, Suryavir; Garg, Nischal (Journal of Neonatal Surgery, 2025)
Introduction : Systemic Inflammatory Response Syndrome (SIRS) represents an amplified immune response to diverse insults such as infection, trauma, surgery, or ischemia. When SIRS is associated with a suspected or confirmed infection, it is referred to as sepsis. Diagnostic criteria for SIRS include any two of the following: a white blood cell (WBC) count of ≥4000/μL or >10% immature band forms, a body temperature >38°C or <36°C, heart rate >90 bpm, respiratory rate >20/min, or a PaCO₂ level <32 mm Hg. While procalcitonin (PCT) serves as a reliable but costly biomarker for sepsis, more economical alternatives include total leukocyte count (TLC), absolute neutrophil count, and the neutrophil-to-lymphocyte ratio (NLR). ObjectivesThis study aimed to investigate the correlation between PCT and hematological markers such as TLC, neutrophil count, and NLR in patients diagnosed with SIRS, with and without confirmed infections, and to assess the utility of these markers in differentiating between non-infective SIRS and sepsis. Methods:A total of 282 acutely ill adult patients meeting the SIRS criteria were enrolled. Within 12 hours of hospital admission, serum PCT levels, TLC, neutrophil counts, and blood cultures were obtained. Additional baseline investigations were also recorded. Results:Of the 282 patients, 194 were classified under SIRS without infection (Group I) and 88 under sepsis (Group II). Statistically significant differences in age and gender distribution were observed between the two groups (p < 0.05). All four parameters—PCT, TLC, neutrophil count, and NLR—were significantly elevated in the sepsis group. Strong correlations were noted between PCT and the hematological markers, particularly with NLR and neutrophil count. Conclusion:PCT remains the most accurate biomarker for diagnosing sepsis, but TLC, neutrophil count, and NLR also demonstrated significant predictive value. These readily available and affordable tests can be effective in identifying sepsis in resource-limited settings.